A New Approach for Trust Prediction by using collaborative filtering based of Pareto dominance in Social Networks - Ghodousi, Elnaz; Hamzeh, Ali (Ciência e Natura, 2015)
Along with the increasing popularity of social web sites, users rely more on the trustworthiness informationfor many online activities among users.[24] However, such social network data often suffers from two problems,(1)severe data sparsity and are not able to provide users with enough information, (2)dataset’s is very large.Therefore, trust prediction has emerged as an important topic in social network research. In this paper weproposed a new approach by using collaborative filtering method and the concept of Pareto dominance. We usesPareto dominance to perform a pre-filtering process eliminating less representative users from the k-neighbourselection process while retaining the most promising ones. The results from experiments performed on FilmTrustdataset and Epinions dataset.